Livestock asset dynamics among pastoralists in Northern Kenya - Samuel Mburu; Micha Kaiser; Alfonso Sousa-Poza (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
Understanding household-level asset dynamics has important implications for designing relevant poverty reduction policies. To advance this understanding, we develop a microeconomic model to analyze the impact of a shock (for example a drought) on the behavioral decisions of pastoralists in Northern Kenya. Using household panel data this study then explores the livestock asset dynamics using both non-parametric and semi-parametric techniques to establish the shape of the asset accumulation path and to determine whether multiple equilibria exist. More specifically, using tropical livestock units as a measure of livestock accumulation over time, we show not only that these assets converge to a single equilibrium but that forage availability and herd diversity play a major role in such livestock accumulation.
urn:nbn:de:bsz:100-opus-14091
Keywords: 330; poverty dynamics; pastoralists; livestock; semi-parametric estimation; Kenya